Management of continental saline ecosystems in the Republic of Serbia – Are these ecosystems suitable for nature-based tourism? - Luković, Milica; Šilc, Urban (Hotel and Tourism Management, 2021)
Continental saline habitats represent unique, authentic and rare ecosystems. These ecosystems are typically distributed in arid and semi-arid regions; however, they are also found in inland areas in temperate climate zones. Usually, the general public is not familiar with this particular type of ecosystem. In order to present saline habitats to tourists, a broadly applied method of ecosystem suitability assessment (ESI – ecosystem suitability index) was used and adjusted to the purposes of this research. The research aims to estimate the nature-based tourism potentials of selected sites. Thus, six representative halophytic habitats distributed along the geographic gradient, from the Pannonian Plain to the south of Serbia, were chosen. In terms of each site, seven indicators (e.g., flora and vegetation, bird fauna, landscape, protection status, accessibility, and ecotourism facilities), important for nature-based tourism, were analyzed. The results show that the Pannonian saline habitats have greater opportunities for development of this type of tourism in almost all categories compared to southern sites.